2011
DOI: 10.3402/qhw.v6i2.7126
|View full text |Cite
|
Sign up to set email alerts
|

Supporting positive dimensions of health, challenges in mental health care

Abstract: This paper will explore two contrasting paradigms in mental health care and their relationship to evidence-based practice. The biomedical perspective of pathogenesis and the health perspective of salotogenesis are two major diverse views in mental health care. Positive dimensions of health are traditionally viewed as software not suitable for statistical analysis, while absence of symptoms of disease are regarded as measurable and suitable for statistical analysis and appropriate as a foundation of evidence-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
17
0
2
Order By: Relevance
“…Salutogenesis provides a new design that enables faster progress toward better health by helping health professionals' practices to be about health (Becker & Rhynders, 2013). Jormfeldt (2011) illuminates this through an example of how a focus on diagnosis (pathogenesis) versus a focus on the person (salutogenesis) might be displayed in clinical mental health work. When looking at schizophrenia from a biomedical point of view, medication and the person's compliance is emphasized.…”
Section: Applying Salutogenesis In Mental Healthcare Settingsmentioning
confidence: 99%
“…Salutogenesis provides a new design that enables faster progress toward better health by helping health professionals' practices to be about health (Becker & Rhynders, 2013). Jormfeldt (2011) illuminates this through an example of how a focus on diagnosis (pathogenesis) versus a focus on the person (salutogenesis) might be displayed in clinical mental health work. When looking at schizophrenia from a biomedical point of view, medication and the person's compliance is emphasized.…”
Section: Applying Salutogenesis In Mental Healthcare Settingsmentioning
confidence: 99%
“…Arneson and Ekberg (2005) and Buchanan (2006) found that social support and supporting group contexts are essential for achievement of personal goals. A strict provider-centred approach that mainly focuses on medical treatment does not increase quality of life and the ability to achieve personal goals among persons diagnosed with schizophrenia (Chee, 2009;Jormfeldt, 2011). Anderson and Funnell (2005) claim that a fundamental redefinition of the roles and relationships of health care professionals and patients is required to sufficiently support processes of empowerment in the care of people with chronic diseases such as schizophrenia.…”
Section: Towards Personal Growthmentioning
confidence: 99%
“…Strengthening the training of professionals in somatic care, as well as going beyond the absence of mental disorder to consider the benefits of positive wellbeing, can only be helpful for lifestyle monitoring and behavioural change [73]. Better training will also reduce the likelihood that these professionals ‘avoid’ dealing with physical health issues through a lack of expertise.…”
Section: Discussionmentioning
confidence: 99%